Perbandingan Sistem Vokoid Minimal Bahasa Indonesia Antara Penyandang Hambatan Majemuk dan Anak Normal - Rahayu - Pujiastuti; Mimas - Ardhianti (Ranah: Jurnal Kajian Bahasa, 2022)
The limitations of people with multiple disabilities cause the development of vocoid production in children to be different from normal children. Therefore, this study aims to describe the differences and similarities of minimal Indonesian vocoid produced by persons with multiple disabilities and normal children. Through these differences and similarities, there was hope can be made that an appropriate response to vocoids the production of multiple disabilities. The approach used is descriptive qualitative with longitudinal data collection methods. The data is in the form of minimal vocoid that provides information on the differences and similarities of the Indonesian minimal vocoid system with multiple disabilities and normal children. Data collection uses observation techniques supported by fishing, recording, and field recording techniques. Data analysis uses techniques of sorting, turning, and connecting. The validity of the data used triangulation of theories, sources, and methods. The results of the study found differences, the minimal vocoid system of normal Indonesian children in sequence [a], [i], [u], while those with multiple disabilities were [a], [o], [u]. The similarity, there is a universal minimum vocoid system in Indonesian with multiple disabilities and normal children based on the position of the tongue and mouth shape due to the use of minimum effort rules. AbstrakKeterbatasan yang dimiliki penyandang hambatan majemuk menyebabkan perkembangan produksi vokoid anak berbeda dengan anak normal. Oleh karena itu, tujuan penelitian ini untuk mendeskripsikan perbedaan dan persamaan vokoid minimal bahasa Indonesia yang dihasilkan penyandang hambatan majemuk dan anak normal. Dengan mengetahui perbedaan dan persamaan tersebut diharapkan dapat dilakukan penyikapan yang tepat terhadap produksi vokoid penyandang hambatan majemuk. Pendekatan yang digunakan deskriptif kualitatif dengan metode pengumpulan data longitudinal. Data berupa vokoid minimal yang memberi informasi perbedaan dan persamaan sistem vokoid minimal bahasa Indonesia penyandang hambatan majemuk dan anak normal. Pengumpulan data menggunakan teknik pengamatan yang didukung teknik pemancingan, perekaman, dan pencatatan lapangan. Penganalisisan data menggunakan teknik pilah, balik, dan hubung. Keabsahan data menggunakan triangulasi teori, sumber, dan metode. Hasil penelitian menemukan perbedaan, yaitu sistem vokoid minimal bahasa Indonesia anak normal berurutan [a], [i], [u], sedangkan penyandang hambatan majemuk [a], [o], [u]. Persamaannya, ada keuniversalan sistem vokoid minimal bahasa Indonesia penyandang hambatan majemuk dan anak normal berdasarkan posisi lidah dan bentuk mulut karena penggunaan kaidah usaha minimal.